Reality Computing: An end-to-end process for Herpetological Heritage - Rodríguez, Graciela (2018)
Documentation of institutional biological collections are essential for scientific studies and conservation of the biodiversity of a region. In particular, preserved specimens require the development of a short- and long-term plan to prevent damage. In this context, the 3D digitisation of this type of documentation provides innovative mechanisms to safeguard the valuable information provided by the collections and at the same time prevent any possible loss of information. At the moment, the potential of laser scanning in model reconstruction is well-known, but developed works using this method for 3D construction reveal a lack of reliable, precise and flexible solutions. Furthermore, visualisation of results is often very useless and does not go beyond web-based applications. This work presents an analysis of 3D modelling using two digitisation techniques: laser scanning and photogrammetry; combined with real time VR and AR visualizations and 3D printing.